Researching and Reshaping Literacy Learning: Three Urban K-6 Teachers’ Ongoing Transformations through Everyday Action Research - Kristin Nicole Rainville; Grace Enriquez (Networks: An Online Journal for Teacher Research, 2016)
Given the vast range of diversity among children’s backgrounds and needs, literacy educators must consider multiple ways in which children learn and interact with texts. Moreover, policies that increasingly require frequent assessments of children’s literacy achievement place pressure on educators to find immediate ways to impact children’s learning. This qualitative inquiry explores three graduate students’ yearlong engagement in literacy-related action research within ethnically and socioeconomically diverse, urban K-6 classrooms. Grounded in a social practice perspective on literacy and a sociocultural perspective on literacy learning, we examined participants’ constructions of action research as they developed research questions, entered various research sites, and engaged in a cyclical process of research-reflection-action in order to impact student learning in those classroom communities. With these case studies, we argue that for teachers to fully embrace and incorporate action research into their practice, they need to go beyond completing the steps to frame action research as a constant way of thinking, a daily practice, and an ongoing process of continuously spiraling mini-cycles that change instruction in incremental, yet ultimately powerful ways.